Steel Fiber Addition in Eco-Friendly Zero-Cement Concrete: Proportions and Properties - Hussein, A.; Abdul Rasoul, Z. M. R.; Alsaad, A. J. (Engineering, Technology & Applied Science Research, 2022)
The main objective of this paper is to study the behavior of eco-friendly zero-cement concrete, its proportions, and its properties. The experimental program involves casting and testing many specimens divided into three main groups according to the percentage of added steel fibers in order to investigate the effect of steel fibers on the density, compressive strength, modulus of elasticity, and splitting tensile strength of concrete. The experimental outcomes indicated that the percentage of steel fibers has a small impact on the dry density: adding 0.5% and 1% of steel fibers increased the dry density by about 0.9% and 1.6% respectively. The percentage of steel fibers has an important impact on the compressive strength: after 28 days, steel fibers increased the compressive strength by about 4.9% and 12.8% for added steel fiber percentages of 0.5% and 1%. Also, the results indicated that steel fiber had an important impact on the splitting tensile strength in concrete after 28 days of curing: adding 0.5% and 1% steel fibers increased the splitting tensile strength by about 11.8%and 23.2% respectively. Finally, adding steel fibers has an impact on the modulus of elasticity: after 28 days, adding 0.5% and 1% steel fibers improved the modulus of elasticity approximately by 1.7% and 5%.